Adropin and risk factors of arterial hypertension in patients with excess body weight and obesity - Pokrovska, Nataliia; Sklyarov, Eugen (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2022)
Introduction. Adropin is a hormone that is involved in the pathogenesis of arterial hypertension (AH) and diseases of the cardiovascular system and energy homeostasis, in particular, it reduces insulin resistance by controlling glucose synthesis in the liver. Aim. To investigate the level of adropin and its interaction with risk factors for AH in overweight and obese patients. Materials and methods. 70 patients with AH and overweight or obesity aged 62.4 ±  10.4 years were examined. 10 practically healthy people were selected for the control group. The level of adropin was determined by enzyme immunoassay (Finetest Elisa Kit) in blood serum. The inclusion criteria for participation in the study were: age of patients 40–75 years; arterial hypertension; BMI > 25 kg/m2. Results. It was established that the average level of adropin in patients with AH and comorbid obesity or excess body weight (n = 70) was 775.5 ± 311.7 pg/ml, which is significantly lower than the content of this peptide in practically healthy individuals (n = 10), which was 1084.6 ± 110.2 pg/ml (p <  0.01). A tendency towards a decrease in the level of the hormone in men was noted. It is probably associated with a much higher prevalence of smoking among this category of people, since when assessing the factors contributing to the development of AH and worsening its prognosis, a significant decrease in adropin was found in persons with a history of smoking (p < 0.01). In obese patients (BMI > 30 kg/m2), the level of adropin was significantly lower (p < 0.05), as well as in individuals with blood pressure > 150/90 mm Hg (p > 0.05). Conclusions. The level of serum adropin is significantly reduced in persons with AH and overweight and obesity compared to practically healthy persons. Factors contributing to a decrease in peptide concentration include smoking, obesity, and elevated blood glucose levels. Blood pressure indicators are not critical for changes in blood hormone concentration, which is probably due to medications used to treat AH.